Telling Tales: Genre and Narrative in Post-Soviet Poetry. (1st April 2013) - Hodgson, Katharine
Abstract : The post-Soviet revival of a group of related genres of narrative poetry is explored, focusing on the work of two poets: Mariia Stepanova, with her connections to the ballad tradition and the uncanny, and Boris Khersonskii, whose cycles and collections document the lost world of Jewish life in southern Russia. There is an exploration of the ways in which narrative poetry, which had been closely associated with official Soviet culture, has now been revitalized by the adoption of elements drawn both from the traditional epic, such as the objective, impersonal narrative voice, and from popular culture, including horror stories and urban myth.